PEMBIASAAN LITERASI MEMBACA PADA ANAK USIA 0-2 TAHUN DI ERA DIGITAL - Rista Erika; Mia Siti Nurazizah; Eva Manfaatin (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
The urgency of cultivating reading literacy habits in children aged 0–2 years amid the challenges of the digital era can significantly influence their learning patterns. This study aims to examine strategies for fostering reading literacy habits in children aged 0–2 years. The research method used is a literature review. The results show that early reading habits strengthen the emotional bond between children and parents, stimulate early language development, and foster an interest in literacy. The role of parents as the main facilitators is crucial. The study emphasizes that early literacy should be integrated through both traditional methods and the wise use of digital technology. The research suggests active parental involvement, the provision of age-appropriate reading materials, and the use of safe literacy applications for children. This study contributes to literacy-based parenting in the digital era. Thus, early literacy can be sustainably instilled to support the optimal development of children aged 0–2 years.